The employment of artificial intelligence in religious and legislative institutions, with fatwa and judiciary as a model. - Ismail, Dr. Mujahid Mahmoud Ismail (Sulaimani Journal for Humanities, 2026)
Praise be to Allah, the Lord of the worlds, and peace and blessings be upon our Prophet Muhammad and upon God and his companions. It is no secret that the development of Information Technology and software has reached at all levels and there is no field except for its committee and took its share in its management or participation in its management. One of the branches of this study (fatwa and judiciary), although the fatwa was more concerning than the judiciary, it was necessary to indicate the relationship that existed between artificial intelligence on the one hand and Fatwa and judiciary on the other, and there was a great need to know the extent of the development of this relationship and whether it is positive in its aspects or has pros and cons. The research papers in which this is a summary trace of this relationship and a statement of the results of this relationship from the employment of artificial intelligence. The second research was to indicate the use of artificial intelligence in the fatwa, the negatives were that the fatwa takes into account the conditions of the respondent and that the facts are similar, and this is something that artificial intelligence cannot differentiate, and one of its positives is that it can be a source of assistance to the owner of the specialty in reaching the most appropriate fatwa, while the third research was to employ artificial intelligence in the elimination of the negatives and positives, one of its negatives is in the field of the judge ruled that artificial intelligence may confuse the branches of laws and their origins from one country to another for the difference of its nutrients, as for its advantages It serves as a guide for the judge to approximate the correct judgment by mentioning what the judge may miss from the laws or rulings that originated elsewhere and in another case.
Keywords: employment; intelligence artificial; fatwa; judiciary